2005
DOI: 10.1103/physrevlett.94.203001
|View full text |Cite
|
Sign up to set email alerts
|

Optical Production of Ultracold Polar Molecules

Abstract: We demonstrate the production of ultracold polar RbCs molecules in their vibronic ground state, via photoassociation of laser-cooled atoms followed by a laser-stimulated state transfer process. The resulting sample of X 1 Σ + (v = 0) molecules has a translational temperature of ∼ 100 µK and a narrow distribution of rotational states. With the method described here it should be possible to produce samples even colder in all degrees of freedom, as well as other bi-alkali species.PACS numbers: 33.80. Ps, 39.25.+k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
455
1
4

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(468 citation statements)
references
References 40 publications
5
455
1
4
Order By: Relevance
“…The experimental data field starts from the lowest vibrational level v * A = 0 of the singlet and nonuniformly covers rotational quantum numbers J ∈ [7,225] in the energy range E J ∈ [10040, 13250] cm −1 . Overall 42 adjusted fitting parameters have been required to reproduce more than 3400 rovibronic termvalues of the A ∼ b complex with a standard deviation of 0.004 cm −1 which is absolutely consistent with the uncertainty of the experiment of 0.003-0.01 cm −1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental data field starts from the lowest vibrational level v * A = 0 of the singlet and nonuniformly covers rotational quantum numbers J ∈ [7,225] in the energy range E J ∈ [10040, 13250] cm −1 . Overall 42 adjusted fitting parameters have been required to reproduce more than 3400 rovibronic termvalues of the A ∼ b complex with a standard deviation of 0.004 cm −1 which is absolutely consistent with the uncertainty of the experiment of 0.003-0.01 cm −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to proximity of K(4p) and Rb(5p) energies, the energy of low-lying electronic states of KCs is similar to the ones in the RbCs molecule, however, KCs possess larger permanent electric dipole moment. The RbCs molecule has been already studied in ultracold conditions [7,8,9]. In particular, the recent quantum dynamics simulation of the mixed A 1 Σ + and b 3 Π Ω states of RbCs in a time-dependent wave-packet approach [6] demonstrated that the pump -dump picosecond pulsed laser scheme could be efficient to form ultracold heteronuclear diatomic molecules in highly bonded ground X 1 Σ + state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,13,14,15,16 and cooling of polar molecules with the goal to create quantum degenerate ground state molecules are currently developed in several laboratories. 17,18,19,20,21,22,23 We show below that for an appropriate choice of static electric and microwave fields the effective interaction reduces to the form as in Eq. (1) with tunable two-body and the three-body interactions.…”
Section: Fig 1: Strengths Of the Dominant Three-body Interactionsmentioning
confidence: 99%
“…A promising strategy for the creation of such molecules is based on the association of ultracold atoms using a Feshbach resonance, or photoassociation and subsequent transfer to a much lower rovibrational level using Raman transitions 16 . If the moleculemolecule interactions are predominantly elastic and effectively repulsive, then a state with one molecule per lattice site can finally be obtained using a quantum phase transition from a superfluid to a Mott insulator by ramping up the depth of an optical lattice 6 .…”
mentioning
confidence: 99%